Experimental study of a dental airotor cooling spray system - Pathak, Binita; Yadav, Saurabh (American Institute of Physics Inc., 2023)
In this paper, we have characterized a spray system used in dental airotors. Experimental data with respect to droplet size and velocity are generated at different locations in the spray. The impact dynamics of the spray upon substrates are also analyzed. The breakup modes have been identified in the system, and appropriate physical insights into the dynamics are provided. The impact of the spray upon both the hard substrates results in highly rebounding daughter droplets, which can contribute to bio-aerosols. The risks of cross-contamination due to aerosol can thus be prevented with appropriate modifications of the spray nozzles.
This paper published with affiliation IIT (BHU), Varanasi in open access mode.
Keywords: Aerosols; Contamination; Drops; Spray nozzles; Bioaerosols; Break-up modes; Cross contamination; Daughter droplets; Droplet velocity; Droplets sizes